Draft Annual Plan 1988-89 (Scheme Details) Vol.-II (Part-I) Government of Manipur - Planning Commission (Planning Commission, 1987)
The objective of the scheme is the dissemination of latest Agricultural Technology to the farmers through Training and updating the technology of the force by feed back process. At present not much employment could be given in the hill districts though they occupy 9/10th of the geographical area due to inadequate staff and infrastructure requirements.
Planning Department Government of Manipur